2015
DOI: 10.1159/000368769
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Neuronal Death and Functional Deficits following Nerve Injury during the Early Postnatal Developmental Period in Rats

Abstract: In contrast to adult rat nerve injury models, neonatal sciatic nerve crush leads to massive motor and sensory neuron death. Death of these neurons results from both the loss of functional contact between the nerve terminals and their targets, and the inability of immature Schwann cells in the distal stump of the injured nerve to sustain regeneration. However, current dogma holds that little to no motoneuron death occurs in response to nerve crush at postnatal day 5 (P5). The purpose of the current study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 68 publications
0
15
0
2
Order By: Relevance
“…Kemp and colleagues [21] showed that the neuroprotective agent P7C3 enhanced motor and sensory neuron survival and produced a partial recovery of animal performance. Furthermore, it has been reported in rats with SNC at P3-P30 [22] that locomotor recovery, assessed with the SFI in P7 rats, was worse than in naive animals, and a decrease in the number of motor and sensory neurons was seen at P7 and P30 as well as a severe impairment of muscle function observed when SNC was inflicted before P30. Overall, there is a lack of systematic experimental data on the effect of SNC on the neuronal circuits involved in locomotor control and recovery of locomotor function indicating a need for better measures of outcome assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Kemp and colleagues [21] showed that the neuroprotective agent P7C3 enhanced motor and sensory neuron survival and produced a partial recovery of animal performance. Furthermore, it has been reported in rats with SNC at P3-P30 [22] that locomotor recovery, assessed with the SFI in P7 rats, was worse than in naive animals, and a decrease in the number of motor and sensory neurons was seen at P7 and P30 as well as a severe impairment of muscle function observed when SNC was inflicted before P30. Overall, there is a lack of systematic experimental data on the effect of SNC on the neuronal circuits involved in locomotor control and recovery of locomotor function indicating a need for better measures of outcome assessment.…”
Section: Introductionmentioning
confidence: 99%
“…However, more proximal postganglionic BPI (C7 spinal nerve) results in delayed 20%–30% death of corresponding motoneurons in adult rats (Jivan et al., 2006; Ma et al., 2001). Recent studies assessing the effects of age on motoneuronal survival following sciatic nerve injury in rats also demonstrate that injury at 3–7 days after birth induced greater neuronal loss that injury at age 30 days (Kemp et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with earlier observations on the differential expression of c‐JUN and ATF‐3 following proximal or distal axotomy (Herdegen et al ., ; Tsujino et al ., ; Zhou et al ., ; Linda et al ., ). In contrast, peripheral axotomy in neonatal (P3‐30) rats leads to similar motoneuron loss and poor function regeneration, emphasizing the importance of the age of the experimental animals and location of the axotomy (Kemp et al ., ).…”
Section: Fundamental Researchmentioning
confidence: 99%
“…This indicates that atrophy following ventral root avulsion could have been mistaken for motoneuron death (McPhail et al, 2004). Motoneuron loss occurs only following a nerve lesion close to the cell body in adult rats or following peripheral nerve axotomy in neonatal (P3-30) rats (Kemp et al, 2015). The precise biological mechanism which underlies the degeneration of motoneurons is still not fully understood.…”
Section: The Ventral Horn: Motoneuron Degeneration and Gliosismentioning
confidence: 99%